2019
DOI: 10.1121/1.5124486
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and characterization of infrasound from a tornado producing storm

Abstract: A hail-producing supercell on 11 May 2017 produced a small (EFU) tornado near Perkins, Oklahoma (35.97,.04) at 2013 UTC. Two infrasound microphones with a 59-m separation and a regional Doppler radar station were located 18.7 km and 70 km from the tornado, respectively.Elevated infrasound levels were observed starting 7 minutes before the verified tornado.Infrasound data below ~5 Hz was contaminated with wind noise, but in the 5-50 Hz band the infrasound was independent of wind speed with a bearing angle that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 68 publications
(94 reference statements)
0
24
0
Order By: Relevance
“…Infrasound, sound below human hearing (< 20 Hz), is one possibility. Infrasound in the nominal range of 0.5 to 10 Hz has been observed coming from the same region as tornadoes that were verified with Doppler radar and/or visual observations (Bedard et al, 2004b, a;Frazier et al, 2014;Goudeau et al, 2018;Elbing et al, 2019). These recent observations suggest that the infrasound signal may carry information specific to the tornado structure and dynamics.…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations
“…Infrasound, sound below human hearing (< 20 Hz), is one possibility. Infrasound in the nominal range of 0.5 to 10 Hz has been observed coming from the same region as tornadoes that were verified with Doppler radar and/or visual observations (Bedard et al, 2004b, a;Frazier et al, 2014;Goudeau et al, 2018;Elbing et al, 2019). These recent observations suggest that the infrasound signal may carry information specific to the tornado structure and dynamics.…”
Section: Introductionmentioning
confidence: 68%
“…Contemporary tornado infrasound results continue to be reported primarily in conference papers (Noble and Tenney, 2003;Bedard et al, 2004b, a;Prassner and Noble, 2004), project reports (Rinehart, 2018), and oral presentations (Rinehart, 2012;Goudeau et al, 2018). Exceptions to this trend include four journal articles focused on infrasound observations from tornadoes (Bedard, 2005;Frazier et al, 2014;Dunn et al, 2016;Elbing et al, 2019). Bedard (2005) showed that infrasound emissions of ≈ 1 Hz followed the available radar observations associated with a tornado.…”
Section: Previous Work and Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…To summarize all that has been said, I want to express the hope that my vision of the nature of the tornado will eventually "curb" this formidable phenomenon, and not only endlessly study its features, as is now happening [17][18][19].…”
Section: Main Bodymentioning
confidence: 99%